Mensageiro da Amazônia: sobrevivência em meio às novas ferramentas de comunicação digital - Souza, Marcos Felipe Rodrigues de (Brasil, 2022)
This monograph sought to investigate how new digital communication tools, especially those that allow the exchange of instant messages such as WhatsApp and Facebook, interfere in the execution process of the radio program Mensageiro da Amazônia, on Rádio Alvorada. The program is one of the most traditional on the broadcaster’s schedule, responsible for issuing notices and communications to thousands of listeners, especially those who live in riverside communities in the region. This work covers the universe of life in the Amazon to point out the relationship between riverside populations and radio, the precursor of mass communication in the region. It navigates through the transformations and adaptations of this vehicle, narrates the history of broadcasting in Amazonas, and arrives in Parintins, which saw the birth of the city’s first radio station in 1967. To further elucidate the proposed investigation, the research compares two distinct realities, found from the visit to riverine communities Mato Grosso, which has low access to telephones, and Nossa Senhora da Conceição, which enjoys excellent signal from the telephone network and services of mobile internet. The study presents results that show the interference of these digital communication tools in the execution and audience of the Messenger of the Amazon. Even so, Rádio Alvorada’s announcement program maintains its active voice in the region and represents one of the main channels of information for the communities that inhabit the banks of rivers in the Amazon.